The Convergence of Ishikawa Iteration for Generalized Φ-contractive Mappings - Linxin Li, Dingping Wu (Results in Nonlinear Analysis, 2021)
Charles[1] proved the convergence of Picard-type iterative for generalized Φ−accretive non-self mappings in a real uniformly smooth Banach space. Based on the theorems of the zeros of strongly Φ−quasi-accretive and fixed points of strongly Φ−hemi contractions, we extend the results to Ishikawa iterative and Ishikawa iteration process with errors for generalized Φ−hemi-contractive mappings.